Tecnica, vita e cura - Guchet, Xavier (Mechane, 2020)
Caring concerns have recently extended to entities that were not formerly considered subjects of care – namely ecosystems, biodiversity and the planet itself. Industrialized societies are indeed urged to give up their predatory relationships to nature and to reconfigure them according to a caring perspective. In this respect, contemporary technologies are likely to be part of the problem, as they are accused of causing serious and even irreversible damage to nature: they are mainly considered antinomic to care. They are basically held responsible for the extension of computational rationality (metron) to all human activities, rendering them impervious to any values that would not be productivity or efficiency-oriented. Yet, from the Antiquity to the modern period, technological activities were above all considered an extension of humans as living beings and as such, they were rather a matter of limitation, prudence and right measure (metrion). How to explain such a reversal from metrion to metron in Western modernity? The paper explores the shifting and complex relationships between technology, life, nature and care from historical, anthropological and philosophical perspectives. It pays particular attention to how technology progressively divorced from the living body in the Age of Enlightenment, and it analyses the redefinition of technology that this divorce resulted in. It argues that Kant accurately grasped this determining shift in the conception of technology, and explains why this shift ended up in making impenetrable the antique relationship between technology and care. It also highlights the extent to which Gilbert Simondon’s approach to technology overcomes this divide and actually rearticulates technology, life and care, paving the way for an original approach to technology that closely links anthropology and ontological accounts on it. In this respect, the paper argues that this anthropo-philosophical perspective on technology, that pervades both contemporary French and Italian developments in the philosophy of technology, may fruitfully contribute to enrich the dominant Anglo-saxon trends of the field, namely analytic philosophy of technology and postphenomenology.